Enantioselective Syntheses of Axially Chiral Phosphonates or Phosphine Oxides via Asymmetric Suzuki Reactions with Chiral Sulfinamide Monophosphine Ligands. Issue 17 (6th May 2019) - Zhang, Yaqi; Li, Yongsu; Pan, Bendu; Xu, Hao; Liang, Hao; Jiang, Xiaoding; Liu, Binyun; Tse, Man‐Kin; Qiu, Liqin
Abstract: A class of chiral sulfinamide monophosphine ligands Ming‐Phos were firstly employed in the asymmetric Suzuki coupling reactions. Using the in‐situ formed catalyst from PdCl2 and ( R, S S )‐M07, 22 axially chiral phosphonates or phosphine oxides were successfully synthesized in 29−99% yields with up to 98% ee. This method provides a simple and efficient protocol for the synthesis of axially chiral biaryl monophosphine oxides. Abstract : A class of chiral sulfinamide monophosphine ligands Ming‐Phos were employed in asymmetric Suzuki coupling reaction. Multiple axially chiral phosphonates or phosphine oxides were successfully synthesized in 29−99% yields with 68−98% ees.